2014
DOI: 10.1111/1756-185x.12435
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in patients with systemic lupus erythematosus: a retrospective review of 62 pregnancies at a single tertiary center in South Korea

Abstract: Our study demonstrated a rate of live births and of flares in pregnant lupus patients comparable to recent reports in Western countries. Proteinuria during and prior to pregnancy and presence of antiphospholipid antibodies were predictive factors for poor pregnancy outcome. Preserved renal function prior to pregnancy resulted in favorable outcomes even in patients with a history of lupus nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…SLE patients with renal damage were 8.5 time (OR = 8.545, CI 1.396-63.373, P = 0.017) more likely to have a severe pregnancy outcome. There is a significant association between APS and poor pregnancy outcomes (P = 0.001), especially abortion (P = 0.017), that was similar to several studies [9,13,21]. This conferred approximately a 5.2-fold increased risk of unfavorable outcomes (OR: 5.18, 95% CI 1.681-13.647, P = 0.001) when compared to APS-negative patients.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…SLE patients with renal damage were 8.5 time (OR = 8.545, CI 1.396-63.373, P = 0.017) more likely to have a severe pregnancy outcome. There is a significant association between APS and poor pregnancy outcomes (P = 0.001), especially abortion (P = 0.017), that was similar to several studies [9,13,21]. This conferred approximately a 5.2-fold increased risk of unfavorable outcomes (OR: 5.18, 95% CI 1.681-13.647, P = 0.001) when compared to APS-negative patients.…”
Section: Discussionsupporting
confidence: 83%
“…Clowse and colleagues were founded that the activity of SLE during pregnancy led to a threefold increase in spontaneous abortion [12]. Fetal loss, including abortion and stillbirth in the study of Park et al was 17.7% [13]. In the present study, abortion incidence is higher than the above-mentioned researches) 38.8%), because many women with frequent abortion were referred to Kashan's rheumatology clinic to find the cause of their fetal loss.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The Lupus Activity Index (LAI) was later validated for use in pregnancy and the puerperium (6 weeks after birth) and is the only one that has been validated for use in pregnancy . Four prior studies have utilized disease activity assessments adapted for use in pregnancy; 3 used the SLE Pregnancy Disease Activity Index (SLEPDAI) and 1 used the LAI in Pregnancy (LAI‐P) , and only 1 included assessment after birth. Most commonly, the SLEDAI and physician global assessment (PGA) have been used to evaluate disease activity in pregnant women with SLE .…”
Section: Introductionmentioning
confidence: 99%
“…Park et al described 62 pregnancies with lupus nephritis and found that proteinuria >0.5 g/d was associated with adverse outcomes. 7 Liu et al showed a similar association between proteinuria and adverse pregnancy outcomes in their cohort with IgA nephropathy. 8 Steroid therapy is the mainstay of treatment.…”
Section: Discussionmentioning
confidence: 75%